Negotiation Issues for Part-Time Workers : The Impact of Occupation - Zeytinoglu, Isik (Relations industrielles / Industrial Relations, 1993)
Focusing on 117 union locals that had collective agreements for part-time and full-time workers in Ontario, this study showed that negotiation issues varied for part-time workers depending on their occupation. Those in non-professional occupations wanted to limit the number or percentage of part-time work in their bargaining units, while for professionals this was an unimportant negotiation issue. Negotiating the same wages and benefits for part-time and full-time workers, and equality in filling full-time vacancies, were similarly important for both groups of workers.